Cyberbullying victimisation and school dropout intention among South Korean adolescents: the moderating role of peer/teacher support. Issue 3 (2nd July 2020) - Lee, Jungup; Chun, JongSerl; Kim, Jinyung; Lee, Jieun
ABSTRACT: Using the social-ecological approach, this study examined the link between cyberbullying victimisation and the intention to drop out of school among school-aged adolescents in South Korea. This study used self-reported data from 11, 132 students aged 10–19 who had participated in the 2016 Korean Children and Youth Rights Study. Multivariate logistic regressions were performed to investigate the relationship between cyberbullying victimisation, social-ecological variables, and school dropout intention. In Step 1, cyberbullying victimisation was positively associated with students' intention to drop out. All family factors (Step 2) and peer/school factors (Step 3) were significantly associated with the intention to drop out, except for peer victimisation. In Step 4, higher levels of peer/teacher support were found to buffer the association between cyberbullying victimisation and dropout intention. Findings from the study suggest that specific prevention and intervention programmes should be developed and implemented to improve adolescents' well-being.